2018
DOI: 10.1186/s13104-018-3276-y
|View full text |Cite|
|
Sign up to set email alerts
|

Seroprevalence and determinants of transfusion transmissible infections among voluntary blood donors in Homabay, Kisumu and Siaya counties in western Kenya

Abstract: ObjectiveSince the implementation of a series of blood donation safety improvements in Kenya, information about seroprevalence and determinants of transfusion transmissible infections among voluntary blood donors especially in high HIV burden regions of Homabay, Kisumu and Siaya counties remain scanty. A cross-sectional study examining HIV, syphilis, hepatitis B and C virus sero-markers and associated determinants was conducted among voluntary blood donors. Their demographic characteristics and previous risk e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 15 publications
5
24
2
Order By: Relevance
“…Donors who stated having been involved in high-risk sex activities such as having multiple sex partners, sexual intercourses without condom use, and sex in exchange for money were almost eight times more likely to test positive for HBsAg than those with no history of high-risk sex behavior, making high-risk sex behavior the most significant predictor of HBsAg positivity in the study. The findings here corroborate a previous local study on the seroprevalence and determinants of TTIs among voluntary blood donors in Kisumu, Siaya, and Homa Bay counties [ 14 ] which reported a significant association between high-risk sex behavior and HBV infection. Likewise, this study finding is comparable to studies in other regions such as Nigeria and Egypt [ 15 – 17 ] that have also associated history of risky sexual behaviors such as sexual intercourses with no condom use and having sexual intercourses in exchange for money in the dynamics of the spread of HBV.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Donors who stated having been involved in high-risk sex activities such as having multiple sex partners, sexual intercourses without condom use, and sex in exchange for money were almost eight times more likely to test positive for HBsAg than those with no history of high-risk sex behavior, making high-risk sex behavior the most significant predictor of HBsAg positivity in the study. The findings here corroborate a previous local study on the seroprevalence and determinants of TTIs among voluntary blood donors in Kisumu, Siaya, and Homa Bay counties [ 14 ] which reported a significant association between high-risk sex behavior and HBV infection. Likewise, this study finding is comparable to studies in other regions such as Nigeria and Egypt [ 15 – 17 ] that have also associated history of risky sexual behaviors such as sexual intercourses with no condom use and having sexual intercourses in exchange for money in the dynamics of the spread of HBV.…”
Section: Discussionsupporting
confidence: 91%
“…The number of reported intravenous drug users among participants in the current study could possibly go high if the barriers of stigma and criminalization are removed. Nevertheless, the finding in this current study compares similarly to a previous study in the same area [14] that reported no significant association between TTIs including HBV and previous exposure to illicit drug use. In the current study, history of injuries such as accidental needle sticks has recorded no significant association with HBV infection.…”
Section: Discussionsupporting
confidence: 80%
“…This prevalence is lower compared to a 5.6% seroprevalence reported among the same group of people in Nakuru and Tenwek Mission hospital, Kenya, using ELISA testing [22] and similar to 2.4% reported among blood donors in Nyeri in 2016 on samples collected in 2014 using Murex HBsAg version 3 which is a rapid and sensitive enzyme immunoassay [23]. On other hand, this prevalence is however higher than the 0.4% reported in Eldoret in 2018 [24] and lower than the 3.46% described in Kisumu, Homabay and Siaya counties in 2018 [25]. These differences in seroprevalence could be attributed to variations in geographical locations and the sensitivity of the screening techniques used in the detection of the HBsAg for the different studies.…”
Section: Discussionsupporting
confidence: 63%
“…Higher prevalence of any TTI was reported in Eastern Ethiopia [11.5%] with the majority [94.5%] due to HBV [22]. In Western Kenya, the seroprevalence of the four TTI in voluntary blood donors was even higher at 9.4%, distributed among HIV, HBV, HCV, and syphilis at 1.15, 3.46, 3.21, and 1.56%, respectively [23]. Prospectively screened donors from 2005 to 2016 in Nigeria showed 14.…”
Section: Africamentioning
confidence: 90%